Synthesis, Identification, Theoretical and Experimental Studies for Carbon Steel Corrosion Inhibition in Sea Water for New Urea and Thiourea Derivatives linkage to 5-Nitro Isatin Moiety - Suaad Mohammed Hussain Al-Majidi (Journal of Global Pharma Technology, 2016)
This research includes synthesis of some new  heterocyclic derivatives of 5-Nitroisatin namely 5-Nitro-3-(Ethyl imino acetate)-2-oxo indole (1), 5-Nitro-3-[(imino Aceto) urea]-2-oxo indole (2), 5-Nitro-3-[(imino Aceto)thiourea]-2-oxo indole (3), and 5-Nitro-3-[(imino Aceto) phenylthiourea]-2-oxo indole (4), and characterized by FTIR, 1H-NMR and  some physical properties. Theoretically, the inhibition efficiency parameters with physical properties were calculated to ensure for possibility using these compounds as inhibitors. Experimentally, studying the chosen compound of the corrosion inhibition efficiency for carbon steel in 3.5% NaCl solution by isatin derivative is chosen theoretically as the best inhibitor using potentiodynamic polarization.Keywords: Isatin derivatives, Schiff bases, Corrosion inhibitor, DFT quantum mechanical calculation.